Performance evaluation of monotone's netsync protocol - Hu, Kwong Liik (Faculty of Computer Science and Information Technology, 2005)
This research conducted to study the architecture of netsync protocol in Monotone and its performance evaluation in peer-to-peer communication. There is no formal study about the implementation of netsync in Monotone and no formal method to evaluate its performance. From thence, we have conducted study on the architectural design of netsync and its performance evaluation in local area network (LAN). We have compared Monotone's performance to BitKeeper, where BitKeeper is used as benchmark. This research has contribute to the method of performance evaluation of Monotone, identifying its performance metrics, possible future research and testifying the feasibility of netsync in Monotone.